Effect of elevated temperature on strength and ductility of axially loaded hybrid fiber reinforced concrete columns. (December 2021) - Krishna, Arathi; Kaliyaperumal, Saravana Raja Mohan
Abstract: This paper presents the results of a research program conducted on the structural behavior of fiber-reinforced concrete columns subjected to elevated temperatures (27 °C, 200 °C, 400 °C, and 800 °C). For this purpose, three groups of reinforced concrete columns were fabricated, and a comparative study has been done on the strength properties under axial load without and with (mono and hybrid) fibers of various types (microsteel, Polypropylene, and Sisal fibers) with a constant volume fraction of 1%. The properties evaluated were the load carrying capacity, load–deflection characteristics, and failure pattern of columns, and the results were compared with the control column without fiber. The experimental study reveals that the columns reinforced with mono microsteel fiber performed well in comparison with the columns with fibers in terms of superior load carrying capacity, ultimate deflection, energy absorption capacity, ductility characteristics, and thermal resistance. Whereas the columns with hybrid fibers did not show any signs of spalling and performed functionally better than the columns without fibers. The addition of sisal, microsteel, and polypropylene fibers in hybrid form provides better fire resistance, strength, and spalling resistance compared to cement concrete columns without fiber.